Uma historiografia das ideias gramaticográficas em instrumentos de ensino de Julio Pires Ferreira (1868-1930) - Mesquita, Fábio Albert (2023)
This paper investigates the grammaticographic ideas of Julio Pires Ferreira (1868-1930), a teacher and grammarian who wrote teaching instruments adopted in Pernambuco schools between the final years of the 19th century and the first three decades of the 20th century. As a general objective, we seek to characterize the author's ideas regarding the proposals for teaching the Portuguese language and the epistemological profile of the grammatical description carried out. To this end, the research is anchored in the theoretical and methodological assumptions of the Historiography of Linguistics, a discipline that aims to investigate the development of linguistic ideas over time (Koerner, 1996, 2014a, 2014b; Swiggers, 2009a, 2010, 2013, 2019). After an epi-historiographical survey of the works authored by Julio Pires Ferreira, publications intended for school use in secondary courses were selected as primary sources for the investigation, which correspond to the titles Notas sobre a Lingua Portugueza (1893; 1894) and Grammatica Portugueza: 2º anno, para uso do Curso medio e do Curso superior (1910; 1917; 1921; 1929). In order to guide the interpretation of the sources, five categories of analysis were defined: (a) educational scenario; (b) presentation strategies; (c) theoretical and methodological profile; (d) grammatical metalanguage; (e) grammatized language. The results indicate that the author's works, from a rhetorical and descriptive point of view, present characteristics typically associated with the linguistic instruments of that period, characterized by being a moment of transition between a rationalist grammaticographic lineage and an empiricist lineage. In relation to teaching proposals, it was possible to notice a shift in proposals throughout the reissues of the works, which stopped claiming the schooling of studies arising from historical-comparative linguistics and started to reproduce the grammatical contents traditionally foreseen in teaching programs and in Practical grammars. This shift, materialized in changes in the selection of content and the compositional form of the works, can be explained by the external conditions of the educational scenario of the period, marked by demands for instruments that followed the exam points for entry into higher education courses. Regarding grammatical description, the results of the analysis attest that, despite rhetorically seeking a theoretical and methodological alignment with scholars linked to historical-comparative studies, the author presents grammaticographic ideas marked by continuities in relation to grammatical descriptions carried out by instruments linked to the lineage rationalist and, to a lesser extent, the Latinized lineage. Furthermore, in relation to grammatical metalanguage, the relative permanence of the categorical and conceptual framework originating from the Greco-Latin tradition and reproduced by previous grammaticographic lineages and contemporary to the author stands out. As for the grammatized language, it is noted that, following the trends of the grammarians who were his contemporaries, Julio Pires Ferreira does not ignore the linguistic uses peculiar to Brazil. However, instead of legitimizing them, the author places them in a secondary position in relation to the idealized norm that is grammatized in his linguistic instruments. To sum up, the author's grammaticographic ideas mirror the ideas of his time and allow us to identify the nuances and movements involving certain conceptions and descriptive practices of this moment in Brazilian grammaticography.